2003
DOI: 10.1016/s0735-1097(02)02922-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of early electrical remodeling: transcriptional downregulation of ion channel subunits reduces ICa,Land Itoin rapid atrial pacing in rabbits

Abstract: L-type calcium current and I(to) are reduced in early phases of electrical remodeling. A major mechanism appears to be transcriptional downregulation of underlying ion channels, which partially preceded ion current changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 32 publications
6
60
0
2
Order By: Relevance
“…Rapid atrial activation causes Ca 2+ loading, which activates the Ca 2+ /calmodulin/calcineurin/NFAT system, causing transcriptional downregulation of the Cav1.2 α-subunit (72,73). Other potential contributors include downregulation of accessory β 1 -, β 2a -, β 2b -, β 3 -, and α 2 δ 2 -subunits (19,66,74,75), Ca 2+ channel dephosphorylation due to type 1 (PP1) and type 2A (PP2A) serine/threonine protein phosphatase activation (28,66), and enhanced Cav1.2 α-subunit S-nitrosylation (76). MicroRNAs (miRNAs) appear to play a major role in AF (77).…”
Section: Molecular Mechanisms Underlying Functional Substrates For Afmentioning
confidence: 99%
“…Rapid atrial activation causes Ca 2+ loading, which activates the Ca 2+ /calmodulin/calcineurin/NFAT system, causing transcriptional downregulation of the Cav1.2 α-subunit (72,73). Other potential contributors include downregulation of accessory β 1 -, β 2a -, β 2b -, β 3 -, and α 2 δ 2 -subunits (19,66,74,75), Ca 2+ channel dephosphorylation due to type 1 (PP1) and type 2A (PP2A) serine/threonine protein phosphatase activation (28,66), and enhanced Cav1.2 α-subunit S-nitrosylation (76). MicroRNAs (miRNAs) appear to play a major role in AF (77).…”
Section: Molecular Mechanisms Underlying Functional Substrates For Afmentioning
confidence: 99%
“…Some investigations revealed decreased expression of Cav1.2 [67,68], α2/δ1 [69], β1(b) [69] and α1d [68], whereas other studies showed unchanged Cav1.2 [70], β1(a,c) [69] or β2a subunit expression of I Ca,L [57,66]. Several factors might explain these discrepancies, including species differences and time-dependent changes in remodeling in animal models.…”
Section: Downregulation Of L-type Ca 2+ Channelmentioning
confidence: 99%
“…1 Interestingly, our data showed that β2 mRNA was decreased, but β3 mRNA was increased, in hypertrophied RA cells, in contrast to a previous study in which the levels of mRNA expression for both the β2 and β3 subunits were equally decreased in a rapid atrial pacing animal model. 4 The function of auxiliary β subunits of the L-type Ca 2+ channel is not only to promote the membrane expression of CaV1.2 subunits, but also to regulate inactivation kinetics. 15,18 Therefore, it is likely that alternation of the β2 and β3 subunits influences the inactivation kinetics in hypertrophied RA cells.…”
Section: Ical Remodeling In Mct-treated Rat Atriamentioning
confidence: 99%
“…2,3 Recent studies demonstrated that the densities of the L-type calcium (Ca 2+ ) current (ICaL), transient outward current (Ito), and voltage-dependent Na + current (INa) are decreased in experimental animal models of atrial tachycardia-related AF. [4][5][6] In contrast to tachycardia-induced ionic remodeling, several clinical and experimental studies have indicated a decrease, no change, or even an increase in the ICaL density in chronic heart failure (CHF), 1,7,8 depending on the experimental conditions. Nonetheless, it is generally agreed that a possible change in ICaL is a key factor in electrical remodeling of cardiac myocytes in CHF and/or hypertrophy.…”
mentioning
confidence: 99%